On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae) - Pereira, Julia S.; Rocha, Carlos E. F.; Pinto, Ricardo L. (Zootaxa, 2019)
Elpidium ostracods are known by their very particular niche (water accumulated in tank-bromeliads), their relatively low dispersal ability and their dependency on amphibians for dispersal and colonization of new bromeliads. All these characteristics make the genus an interesting group for evolutionary, ecological and even taxonomic studies. However, the diversity of the group remains poorly studied. Here, we describe three new species of Elpidium, Elpidium littlei n. sp., Elpidium heberti n. sp. and Elpidium wolfi n. sp., and re-describe Elpidium laesslei, all from Jamaica. These species are characterized by a copulatory process with separated ejaculatory duct and distal glans, a feature so far unique within the genus. Each species can, in turn, be diagnosed by soft part and carapace morphology, most notably comparing hemipenis, valve ornamentation and degree of sexual dimorphism. The observed morphological diversity of Elpidium is discussed in relation to previous genetic estimates that suggested an even higher diversity in Jamaica. We point to intraspecific variation and lack of complete morphological descriptions as possible explanations. We also reaffirm the need of multidisciplinary studies in order to do more objective and secure taxonomic classifications in future studies.